Violent people: Are they born or made? (Journal of Parents and Teachers, 2026)
It analyses whether violence is innate or develops over time, pointing out that it arises from various biological, psychological and sociocultural factors. It highlights the influence of family, education and social environment. It also analyses violence in schools and proposes prevention through values, dialogue and participation.
Keywords: Violence, Education and Prevention.